Methods Of Teaching Mathematics In Primary Education, Learning Using Mathematical Games - Axundjanov Ibragim Maratovich (Genius Publishing Group, 2024)
Mathematics, a fundamental subject that forms the backbone of various disciplines, has long been considered a challenging and daunting task for many students. The primary education stage is crucial in laying the foundation for future mathematical understanding, and it is essential to adopt effective teaching methods that foster a deep appreciation and comprehension of mathematical concepts. One such approach that has gained popularity in recent years is the use of mathematical games as a tool for learning mathematics in primary education. This article will explore the benefits and methods of incorporating mathematical games into primary education, highlighting their potential to enhance student engagement, motivation, and overall mathematical proficiency
Keywords: math subjects; effective teaching methods; games